Dirofilariasis mouse models for heartworm preclinical research - Marriott, A. E.; Dagley, J. L.; Hegde, S.; Steven, A.; Fricks, C.; DiCosty, U.; Mansour, A.; Campbell, E. J.; Wilson, C. M.; Gusovsky, F.; Ward, S. A.; Hong, W. D.; et al. (Frontiers in Microbiology, 2023)
Dirofilariasis, including heartworm disease, is a major emergent veterinary parasitic infection and a human zoonosis. Currently, experimental infections of cats and dogs are used in veterinary heartworm preclinical drug research. As a refined alternative in vivo heartworm preventative drug screen, we assessed lymphopenic mouse strains with ablation of the interleukin-2/7 common gamma chain (c) as susceptible to the larval development phase of D. immitis. Non-obese diabetic (NOD) Severe Combined ImmunoDeficient (SCID)c-/- (NSG and NXG) and recombinase-activating gene (RAG)2-/-c-/- mouse strains yielded viable D. immitis larvae at 2-4 weeks post-infection, including use of different batches of infectious inoculates, different isolates of D. immitis and at independent laboratories. Mice did not display any clinical signs associated with infection up to 4 weeks. Developing larvae were found in subcutaneous and muscle fascia tissues, the natural site of this stage of heartworm in dogs. Compared with in vitro propagated larvae at day 14, in vivo derived larvae had completed the L4 moult, were significantly larger and contained expanded Wolbachia endobacteria titres. We established an ex vivo L4 paralytic screening system whereby assays with moxidectin or levamisole highlighted discrepancies in relative drug sensitivities in comparison with in vitro reared L4 D. immitis. We demonstrated effective depletion of Wolbachia by 70-90% in D. immitis L4 following 2-7 day oral in vivo exposures of NSG or NXG infected mice with doxycycline or the rapid-acting investigational drug, AWZ1066S. We validated NSG and NXG D. immitis mouse models as a filaricide screen by in vivo treatments with single injections of moxidectin, which mediated 60-88% reduction in L4 larvae at 14-28 days. Future adoption of these mouse models will benefit end-user laboratories conducting research and development of novel heartworm preventatives via increased access, rapid turnaround and reduced costs and may simultaneously decrease the need for experimental cat or dog use.